SOFT MAGNETIC COMPOSITE (SMC) ANALISIS DENGAN BIBLIOMETRIC - Waloyo, Hery Tri; Kurniawan, Krisna Budi; Ahmad, Fauzi; Putra, Ferdiansyah; Fauzan, M. Afif; Firmansyah, Muhammad Gilang; Mujianto, Agus (Jurnal Rekayasa Mesin, 2025)
Soft Magnetic Composite (SMC) is a composite material made by binding iron (Fe) powder with non-magnetic materials such as epoxy resin. The main properties of SMC, which have high electrical resistance yet can efficiently conduct magnetic fields, make it a primary choice for various applications that require efficiency, reliability, and high performance. Extensive research has been conducted on SMC, making it necessary to perform a bibliometric analysis to categorize and observe developments in SMC research. The main objectives of this study are to understand patterns in scientific publications, identify the most productive research developments, determine research linkages, and identify collaboration networks related to SMC. A total of 1067 documents, 347 sources, and 2113 authors were recorded in the Scopus database between 2005 and 2024. The number of article publications has increased annually by 4.36%. China is the most productive country and also has the most extensive international collaboration networks. The majority of publications are published in journals with specific topics, primarily focusing on magnetics and magnetic materials.